Spatiotemporal distribution of small ubiquitin‐like modifiers during human placental development and in response to oxidative and inflammatory stress. (6th April 2018) - Baczyk, Dora; Audette, Melanie C.; Coyaud, Etienne; Raught, Brian; Kingdom, John C.
Abstract : Key points: The post‐translational modification of target proteins by SUMOylation occurs in response to stressful stimuli in a variety of organ systems. Small ubiquitin‐like modifier (SUMO) isoforms 1–4 have recently been identified in the human placenta, and are upregulated in the major obstetrical complication of pre‐eclampsia. This is the first study to characterize the spatiotemporal distribution of SUMO isoforms and their targets during placental development across gestation and in response to stress induced by pre‐eclampsia and chorioamnionitis. Keratins were identified as major targets of placental SUMOylation. The interaction with SUMOs and cytoskeletal filaments provides evidence for SUMOylation possibly contributing to underlying dysfunctional trophoblast turnover, which is a hallmark feature of pre‐eclampsia. Further understanding the role of individual SUMO isoforms and SUMOylation underlying placental dysfunction may provide a target for a novel therapeutic candidate as an approach for treating pre‐eclampsia complicated with placental pathology. Abstract: SUMOylation is a dynamic, reversible post‐translational modification that regulates cellular protein stability and localization. SUMOylation occurs in response to various stressors, including hypoxia and inflammation, features common in the obstetrical condition of pre‐eclampsia. SUMO isoforms 1–4 have recently been identified in the human placenta, but less is known about their role in response to pre‐eclamptic stress. We hypothesized that SUMOylation components have a unique spatiotemporal distribution during placental development and that their subcellular localization can be further modulated by extra‐cellular stressors. Placental SUMO expression was examined across gestation. First‐trimester human placental explants and JAR cells were subjected to hypoxia or TNF‐α cytokine, and subcellular translocation of SUMOs was monitored. SUMOylation target proteins were elucidated using mass spectrometry and proximity ligation assay. Placental SUMO‐1 and SUMO‐4 were restricted to villous cytotrophoblast cells in first trimester and syncytium by term, while SUMO‐2/3 staining was evenly distributed throughout the trophoblast across gestation. In placental villous explants, oxidative stress induced hyperSUMOylation of SUMO‐1 and SUMO‐4 in the syncytial cytoplasm, whereas SUMO‐2/3 nuclear expression increased. Oxidative stress also upregulated cytoplasmic SUMO‐1 and SUMO‐4 protein expression ( P  < 0.05), similar to pre‐eclamptic placentas. Keratins were identified as major targets of placental SUMOylation. Oxidative stress increased the cytokeratin‐7 to SUMO‐1 and SUMO‐4 interactions, while inflammatory stress increased its interaction with SUMO‐2/3. Overall, SUMOs display a unique spatiotemporal distribution in normal human placental development. Our data indicate SUMOylation in pre‐eclampsia, which may impair the stability of cytoskeleton filaments and thus promote trophoblast shedding into the maternal circulation in this condition. Key points: The post‐translational modification of target proteins by SUMOylation occurs in response to stressful stimuli in a variety of organ systems. Small ubiquitin‐like modifier (SUMO) isoforms 1–4 have recently been identified in the human placenta, and are upregulated in the major obstetrical complication of pre‐eclampsia. This is the first study to characterize the spatiotemporal distribution of SUMO isoforms and their targets during placental development across gestation and in response to stress induced by pre‐eclampsia and chorioamnionitis. Keratins were identified as major targets of placental SUMOylation. The interaction with SUMOs and cytoskeletal filaments provides evidence for SUMOylation possibly contributing to underlying dysfunctional trophoblast turnover, which is a hallmark feature of pre‐eclampsia. Further understanding the role of individual SUMO isoforms and SUMOylation underlying placental dysfunction may provide a target for a novel therapeutic candidate as an approach for treating pre‐eclampsia complicated with placental pathology.